Fabrication, characterization and application of Pickering emulsion gels stabilized by defatted grape seed powder - Sheng Geng; Yuxiang Wang; Benguo Liu (Food Chemistry: X, 2024)
The feasibility of defatted grape seed powder (DGSP) stabilizing Pickering emulsion gels as butter substitute was investigated. The Pickering emulsion gel was constructed using DGSP through high-speed homogenization, and the effects of particle concentration (c) and oil-phase (Medium chain triglyceride) volume fraction (φ) on its structure and properties were investigated. Its application as a butter substitute was also evaluated. The results showed that DGSP had various particle shapes, a wide particle size distribution (3–130 μm), and a three-phase contact angle of 128.9 ± 2.3°. The O/W Pickering emulsion gels with φ ≥ 60% could be obtained at c ≥ 2%. The droplet diameter was negatively correlated with c and positively correlated with φ, while the gel strength was positively related to c and φ. The resulting emulsion gel demonstrated solid-like viscoelastic behavior and pseudoplasticity, and had the potential to serve as a butter substitute. The results can promote the application of grape seeds in food.